Existing Condition of Commercial Sericulture Production in Northeastern Thailand - Sumranpath, Krittayaporn; Aungsuratana, Am-on; Auttathom, Tipvadee; Poramacom, Nongnooch (Kasetsart Journal of Social Sciences, 2015)
The objectives of the investigation were: 1) to determine the existing technology and local wisdom applications in commercial sericulture production in the study area; 2) to investigate appropriate technology in commercial sericulture production; and 3) to identify constraints and recommendations on commercial sericulture. The target group was sericulture farmers in Huafai village, Pordang subdistrict, Chonnabot district, Khon Kaen province. The sample size was determined according to Arkin. Forty-eight sericulture farmers were selected through a multistage sampling technique. Key stakeholders in commercial sericulture—namely, three government officials and two intermediaries, were purposively selected. Data collection was performed by interviewing the sericulture farmers, as well as by conducting in-depth interviews with key stakeholders. Descriptive statistics were used along with content analysis. The findings revealed that the farmers applied integrated methods consisting of local wisdom and technology to reduce costs and improve the quality of production, divided into three aspects: 1) in terms of silkworm rearing, farmers should scatter calcium carbonate or talcum powder on silkworms after the molting stage; 2) in the silk yarn reeling process, farmers used the developed reeling apparatus and soaked silk yarns in water after reeling; and 3) in the silk fabric weaving process, farmers mixed olive oil or vinegar with dyes in the dying process; they used rice-wash water in silk yarn combing, and made their own weaving supplies. The main production constraints were: silkworm disease, the high cost of production, mulberry disease, and limited capital. A strategic policy for commercial sericulture production support should focus on: 1) research and development sericulture disease protection and warp yarn production; 2) group empowerment for bargaining; 3) providing soft loans; 4) supporting more marketing channels; and 5) establishing a marketing information center.